Pengaruh Perputaran Kas dan Perputaran Modal Kerja Terhadap Profitabilitas Pada PT Unilever Indonesia Tbk Periode 2014-2023 - Faris, Muhammad; Astuti, Eni Puji (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study is to determine the effect of cash turnover and working capital turnover on profitability at PT Unilever Indonesia Tbk from 2014 to 2023, both partially and simultaneously. The research method used is quantitative, with the sample consisting of the financial statements of PT Unilever Indonesia Tbk for the period 2014-2023. The data analysis techniques used are: classical assumption test, multiple linear regression test, multiple correlation coefficient test, coefficient of determination test, and hypothesis test. Based on the t-test results, cash turnover (X1) has a positive and no significant effect on the return on assets (ROA) (Y) variable at PT Unilever Indonesia Tbk. This is proven by the t-value of 0.804 < 2.364 and the significance value of 0.448 > 0.05. Based on the t-test results, working capital turnover (X2) has a positive and significant effect on the return on assets (ROA) (Y) variable at PT Unilever Indonesia Tbk. This is evidenced by at value of 5.269 > 2.364 and a significance level of 0.001 < 0.05. Based on the results of the F test, the cash turnover (X1) and working capital (X2) variables have a positive and significant effect on return on assets (ROA) (Y) at PT Unilever Indonesia Tbk. This is evidenced by the F value of 15.237 > 4.74 and a significance value of 0.003 < 0.05.